2012
DOI: 10.1093/brain/aws099
|View full text |Cite
|
Sign up to set email alerts
|

The Gulf War era multiple sclerosis cohort: age and incidence rates by race, sex and service

Abstract: We characterize here a new nationwide incident cohort of multiple sclerosis from the US military-veteran population. This cohort provides an update to the only other US nationwide incidence study of multiple sclerosis performed during the 1970s. Medical records and data from the Department of Defense and Department of Veterans Affairs for cases of multiple sclerosis who served in the military between 1990, the start of the Gulf War era, and 2007 and who were service-connected for this disorder by the Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 30 publications
3
126
3
2
Order By: Relevance
“…7 Likewise, a contemporary study of 2,691 Gulf War-era military veterans with MS found that the incidence rate per 100,000 was higher in African Americans (12.1) than in Caucasian Americans (9.3), Hispanic Americans (8.2), Asian Americans (3.3), or Native Americans (3.1). 8 These findings and support the increasing awareness of MS among other minority populations. 7 Regarding clinical manifestations of disease, African Americans are more likely to have an older age at disease onset, whereas Hispanic Americans may have an earlier age at disease onset compared with other patient cohorts.…”
Section: Overview Of Clinical and Genetic Influences On Disease Progrmentioning
confidence: 67%
See 3 more Smart Citations
“…7 Likewise, a contemporary study of 2,691 Gulf War-era military veterans with MS found that the incidence rate per 100,000 was higher in African Americans (12.1) than in Caucasian Americans (9.3), Hispanic Americans (8.2), Asian Americans (3.3), or Native Americans (3.1). 8 These findings and support the increasing awareness of MS among other minority populations. 7 Regarding clinical manifestations of disease, African Americans are more likely to have an older age at disease onset, whereas Hispanic Americans may have an earlier age at disease onset compared with other patient cohorts.…”
Section: Overview Of Clinical and Genetic Influences On Disease Progrmentioning
confidence: 67%
“…For example, African Americans had a mean age at symptom onset of 38.3 years in the retrospective cohort study, 7 and 30.8 and 29.9 years for African American men and women, respectively, in the study of Gulf War-era military veterans. 8 Notably, although the ages at symptom onset and MS diagnosis vary between patient populations, the length of diagnostic delay appears to be consistent between groups in the various studies. Mean time from symptom onset to diagnosis was 2.0 years in the retrospective cohort study 7 and 2.6 years in the military veterans study.…”
Section: Overview Of Clinical and Genetic Influences On Disease Progrmentioning
confidence: 71%
See 2 more Smart Citations
“…13 reflect the prevalence ratio of women to men in MS (2.3-3.5:1) (Ahlgren, Oden, & Lycke, 2011;Wallin et al, 2012). Half of the sample was unemployed or retired due to MS (n=19, 56%).…”
Section: Running Head: Adjustment In Progressive Msmentioning
confidence: 99%